Project-Based Learning Design for Teaching ESP at Engineering Department of Politeknik Negeri Jakarta - Yogi Widiawati; Siti Aisiyah; Ardina Askum (Soshum: Jurnal Sosial dan Humaniora, 2022)
Nowadays, English teachers must be creative to engage students to be more active and critical. Along with technology development, teachers are at ease with their jobs. This mini research aims to make a teaching-learning model of English subject for Specific Purposes (ESP) based on a project (PjBL) for being used in some departments of engineering at Politeknik Negeri Jakarta (PNJ), namely: Civil Engineering Department, Electrical and Electronic Department, IT Engineering Department and Mechanical Department. Such a model has not been made yet before. This research used the descriptive qualitative method. The data was taken from the questionnaires and interviews. The data was analyzed and the design of PjBL and a job sheet as well were made.  The outcome of this research is a kind of teaching-learning model design which will hopefully be going be used as a standard for English teachers of engineering for ESP teachers at Politeknik Negeri Jakarta.